Nasal Bacterial Microbiome Differs Between Healthy Controls and Those With Asthma and Allergic Rhinitis - Chen, Meiping; He, Shiyi; Miles, Phoebe; Li, Chunlin; Ge, Yijun; Yu, Xuechan; Wang, Linfeng; Huang, Weina; Kong, Xue; Ma, Shanni; Li, Yiting; Jiang, Qingwen; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Perturbation of the microbiome has numerous associations with the phenotypes and progression in chronic airways disease. However, the differences in the nasal microbiome in asthma and allergic rhinitis (AR) have not been defined. We examined whether the nasal microbiome would vary among different comorbidities in asthma and AR and that those differences may be associated with the severity of asthma. Nasal lavage fluid was collected from 110 participants, including 20 healthy controls, 30 subjects with AR, 30 subjects with asthma and 30 subjects with combined asthma + AR. The Asthma Control Questionnaire (ACQ-7) was used to evaluate asthma control status. Using 16S rRNA bacterial gene sequencing, we analyzed nasal microbiome in patients with asthma, AR, combined asthma + AR, and healthy controls. Bacterial diversity was analyzed in corresponding with α diversity indices (Chao and Shannon index). Compared with healthy controls, the Chao index tended to be lower in subjects with AR (P = 0.001), asthma (P = 0.001), and combined asthma + AR (P = 0.001) when compared with healthy controls. Furthermore, the Shannon index was significantly lower in subjects with asthma (P = 0.013) and comorbid asthma with AR (P = 0.004) than the control subjects. Disparity in the structure and composition of nasal bacteria were also observed among the four groups. Furthermore, patients with combined asthma + AR and isolated asthma were divided into two groups according to the level of disease control: partially or well-controlled and uncontrolled asthma. The mean relative abundance observed in the groups mentioned the genera of Pseudoflavonifractor were dominated in patients with well and partially controlled disease, in both isolated asthma and combined asthma + AR. In subjects with uncontrolled asthma and combined asthma + AR, a lower evenness and richness (Shannon index, P = 0.040) was observed in nasal microbiome composition. Importantly, lower evenness and richness in the nasal microbiome may be associated with poor disease control in combined asthma + AR. This study showed the upper airway microbiome is associated with airway inflammation disorders and the level of asthma control.